Effect of short-term cypermethrin exposure on oxidant-antioxidant balance in the whole body of rainbow trout fry (Oncorhynchus mykiss) - Sakin, Fatih; Ispir, Ünal; Yonar, Serpil Mişe; Enis Yonar, M.; Reşk Taysi, M. (My University, 2011)
The objective of this study was to investigate the propensity of cypermethrin (CYP) to induce whole body oxidative stress in rainbow trout following exposure. We investigated the effect of CYP (10%, 5%, 2% and 1% of the 4-day rainbow trout flow-through LC 50 1.46 ?g/L CYP) on antioxidants in rainbow trout fry, Oncorhynchus mykiss, using standard laboratory conditions. 24 h exposure caused induction of malondialdehyde (MDA) and various antioxidant enzymes such as catalase (CAT), glutathione peroxidase (GSH-Px) and reduced glutathione (GSH) in the whole body. Fish were monitored for clinical signs. Results obtained showed that CYP significantly (p < 0.05) increased MDA level. Compared to controls, activities of GSH, GSH-Px, and CAT were significantly (p < 0.05) reduced in the whole bodies of rainbow trout fry exposed to CYP. © by PSP.
Keywords: Catalase; Cypermethrin; Glutathione peroxidase; Oxidative stress; Rainbow trout; Reduced glutathione